HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG ANC DENGAN FREKUENSI KUNJUNGAN ANC: The Relationship Between Knowledge and Attitudes of Pregnant Women About Antenatal Care with Frequency of Antenatal Care Visit - Nanang Muhibuddin; Astri Yunita; Dily Ekasari; Liya Ni’matul Maula; Endah Susanti (Forind Press, 2023)
Antenatal Care aims to detect early on the occurrence of a high risk of pregnancy, childbirth, monitor the condition of the fetus, and reduce maternal mortality. The purpose of this study was to determine the relationship between knowledge and attitudes of pregnant women about ANC with the frequency of ANC visits. The research subjects were postpartum mothers at BPM Dotik Sukismi. The research method used a cross sectional approach and the sample was taken with a total sampling technique of 30 respondents. The independent variables are knowledge and attitudes, the dependent variable is ANC visits. Data were collected using a questionnaire and analyzed using the chi square test. With the condition that if accepted, p 0.005 if rejected, p 0.005. The results of the study showed that there was a good relationship between knowledge and the number of ANC visits by 80%. The relationship between a positive attitude and the number of ANC visits is 86.7%. There is a relationship between knowledge and attitudes with the number of ANC visits with a p value of 0.002 (p 0.005). The conclusion of this study shows that there is a relationship between knowledge and attitudes of pregnant women about ANC with the frequency of ANC visits.